Association of inotrope use with neurodevelopmental outcomes in infants <29 weeks gestation: a retrospective cohort study. (12th December 2022) - Doucette, Stefani M.; Kelly, Edmond N.; Church, Paige T.; Lee, Shoo; Shah, Vibhuti
Abstract: Objective: The primary objective was to compare neurodevelopmental (ND) outcomes at 18–24 months in preterm infants <29 weeks gestational age (GA) who received versus those who did not receive inotropes in the first week of life. The secondary objective was to assess ND outcomes according to the duration of inotropic support in the first week of life (≤3 or >3 days). Study design: Retrospective population-based cohort study of preterm infants <29 weeks GA admitted to participating neonatal intensive care units (NICUs) of the Canadian Neonatal Network (CNN) from January 2010 to September 2011 with follow-up data available at 18–24 months. Neurodevelopmental outcomes were assessed using the Bayley Scales of Infant and Toddler Development-Third Edition (BSID-III). Long-term outcomes were categorized as neurodevelopmental impairment (NDI) and significant neurodevelopmental impairment (sNDI), and effect modification due to other neonatal morbidities including receipt of antenatal steroids, GA, small for gestational age (SGA) status, sex, score for neonatal acute physiology (SNAP-II) >20, postnatal steroids, bronchopulmonary dysplasia (BPD), intraventricular hemorrhage (IVH) grade ≥3/periventricular leukomalacia (PVL), early- and late-onset sepsis, retinopathy of prematurity (ROP) and necrotizing enterocolitis (NEC) was assessed. Maternal and infant demographic characteristics and short- and long-term outcomes were compared using Pearson's Chi-square test for categorical variables and Student's t -test or the Wilcoxon rank test for continuous variables. Adjusted odds ratios (AORs) and 95% confidence intervals (CIs) were calculated using multivariable regression analysis. Results: Of the 491 (18.7%) eligible preterm infants who received inotropes during the first week of life, 314 (64%) survived to NICU discharge and 245 (78%) had ND outcome data available. A total of 1775 eligible preterm infants did not receive inotropes in the first week of life; 1647 (92.7%) survived to NICU discharge and 1149 (70%) had ND outcome data. Maternal and infant characteristics associated with infants receiving inotropes included: younger maternal age, clinical chorioamnionitis, no antenatal steroids, outborn, lower GA, BW and Apgar scores at both one and five minutes; and higher SNAP-II scores ( p < .05). Infants who received inotropes in the first week of life were more likely to be require postnatal steroids, had higher rates of BPD, IVH grade ≥3/PVL, early- and late-onset sepsis, ROP, NEC and mortality ( p < .05). Infants who received inotropes in the first week of life also had higher rates of sensorineural or mixed hearing loss with an AOR (95% CI) of 1.99 (1.13, 3.49). After adjusting for confounding variables, there was no difference in the risk of NDI or sNDI between infants who did and did not receive inotropes in the first week of life. Of the infants with neurodevelopmental outcome data available, 186 received inotropes for ≤3 days and 59 for >3 days. After adjusting for confounding variables there was no difference in the risk of NDI or sNDI. Infants who received inotropes for >3 days were more likely to have lower BSID-III cognitive [AOR 2.43 95% CI (1.03, 5.76)] and motor scores <85 [AOR 2.38 95% CI (1.07, 5.30)] respectively. Conclusions: In this large, population-based cohort, infants who received inotropes in the first week of life were at increased risk for sensorineural or mixed hearing loss. There was no difference in NDI or sNDI after adjusting for confounding variables. A longer duration of inotrope use in the first week of life was associated with lower BSID-III cognitive and motor scores, but no difference in overall NDI or sNDI.